The Search for Deliberative Democracy in China
X, 343 p.
Keywords: This book investigates whether the theory of deliberative democracy - developed in the West to focus democratic theory on the legitimation that deliberation can afford - has any application to Chinese processes of democratization. It discovers pockets of theory useful to guide Chinese practices, and also Chinese practice that can educate the West.